Harnessing natural variation to identify cis regulators of sex-biased gene expression in a multi-strain mouse liver model - Matthews, Bryan J.; Waxman, David J. (bioRxiv, 2021)
Sex differences in gene expression are widespread in the liver, where a large number of autosomal factors act in tandem with growth hormone signaling to regulate individual variability of sex differences in liver metabolism and disease. Here, we compare hepatic transcriptomic and epigenetic profiles of mouse strains C57Bl/6J and CAST/EiJ, representing two subspecies separated by 0.5-1 million years of evolution, to elucidate the actions of genetic factors regulating liver sex differences. We identify 144 protein coding genes and 78 lncRNAs showing strain-conserved sex bias; many have gene ontologies relevant to liver function, are more highly liver-specific and show greater sex bias, and are more proximally regulated than genes whose sex bias is strain-dependent. The strain-conserved genes include key growth hormone-dependent transcriptional regulators of liver sex bias; however, three other transcription factors, Trim24, Tox, and Zfp809, lose sex-biased expression in CAST/EiJ mouse liver. To elucidate these strain specificities in expression, we characterized the strain-dependence of sex-biased chromatin opening and enhancer marks at cis regulatory elements (CREs) within expression quantitative trait loci (eQTL) regulating liver sex-biased genes. Strikingly, 208 of 286 eQTLs with strain-specific, sex-differential effects on expression were associated with a complete gain, loss, or reversal of expression sex differences between strains. Moreover, 166 of the 286 eQTLs were linked to the strain-specific gain or loss of localized sex-biased CREs. Remarkably, a subset of these CREs lacked strain-specific genetic variants yet showed coordinated, strain-dependent sex-biased epigenetic regulation. Thus, we directly link hundreds of strain-specific genetic variants to the high variability in CRE activity and expression of sex-biased genes, and uncover underlying genetically-determined epigenetic states controlling liver sex bias in genetically diverse mouse populations. Male-female differences in liver gene expression confer sex differences in diverse biological processes relevant to human health and disease, but are difficult to model in inbred mice given their identical genetic backgrounds. Outbred mice provide some variability, but cross-strain studies of sex bias in rodents have not been well studied. Here we elucidate the actions of genetic factors regulating liver sex differences in two Diversity Outbred mouse founder mouse strains, C57Bl/6 and CAST/EiJ. We find that many of the strain differences in sex-biased gene expression can be linked to the gain or loss of a cis regulatory element associated with one or more strain-specific sequence variants. Strikingly, in many cases, the associated cis regulatory element lacked strain-specific variants, yet was subject to coordinated, strain-dependent epigenetic regulation. Thus, harnessing the power of naturally occurring genetic diversity of Diversity Outbred mice, we integrated biological data at the genetic, epigenetic, and transcriptomic levels across evolutionary divergent mouse strains to discover hundreds of localized genomic regions that control phenotypic sex differences in the liver. These findings may serve as a model for studies of human genetic variation and the effect of population-wide variation on sex differences in health and disease.